A review of the state of the art of solid-state caloric cooling processes at room-temperature before 2019. (October 2019) - Greco, A.; Aprea, C.; Maiorino, A.; Masselli, C.
Highlights: A state of the art of all the developed solid-state caloric prototypes was presented. The devices were classified as magnetocaloric, electrocaloric, elastocaloric or barocaloric. The main design features and the energy performances shown were reported for each device. A point of view of the future perspectives is proposed in the conclusions. Abstract: The solid-state processes for cooling and heat pump technologies are based on the well-known caloric effects (magneto-, electro-, elasto- and baro-caloric). With an interest arisen in 1976, year of the development of the first room-temperature magnetic refrigerator, up to a few years ago, magnetocaloric was among the most investigated caloric cooling techniques and it was considered among the main solid-state alternatives to vapor-compression cooling and heat-pumping. During such period, a remarkable number of prototypes of magnetic refrigerators or heat pumps was built. Recently, the attention toward all the four caloric effects has recently grown; therefore, an increase in projects on solid-state prototype developing (not only on magnetocaloric) was observed. The intention of this paper is to offer a state-of-the-art of all the solid-state prototypes for cooling and heat pumps processes, devoted to room temperature operations, developed before the year 2019.